Trans-Pacific Partnership, Free Trade Zone in Asia-Pacific and the Prospects of their Practical Implementation - A. Ivanov (Международная аналитика)
The article gives a brief description of the essence of the agreement on the Trans-Pacific Partnership, reached on November 5, 2015. The possible positive and negative results of its practical implementation for the member countries of this project, primarily for the US and Japan, and the countries that have not joined the Partnership are analyzed. Particular attention is paid to the possible positive and negative aspects of the TTP impact on Russia and China. Recommendations how Russia and China could avoid the negative impact of the TTP are given. The article also deals with the problems and prospects of the Asia-Pacific free trade zone project (FTAAP).